2021
DOI: 10.1016/j.ultrasmedbio.2021.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Radiotherapeutic Megavoltage Beam on Ultrasound Contrast Agents

Abstract: Collateral damage to healthy surrounding tissue during conventional radiotherapy increases when deviations from the treatment plan occur. Ultrasound contrast agents (UCAs) are a possible candidate for radiation dose monitoring. This study investigated the size distribution and acoustic response of two commercial formulations, SonoVue/Lumason and Definity/Luminity, as a function of dose on clinical megavoltage photon beam exposure (24 Gy). SonoVue samples exhibited a decrease in concentration of bubbles smaller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The influence of radiation on commercial microbubbles was previously reported by Collado-Larra et al 29 Their study demonstrated that irradiating the ultrasound contrast agent SonoVue (known as Lumason in the United States) to >25 Gy, influenced its size distribution and acoustic response more than irradiated Definity. A decrease in the concentration of SonoVue bubbles with diameter < 7 μm was observed, while the acoustic scatter decreased by 3.5 dB after 24 Gy, and the acoustic attenuation increased by 0.15 dB/cm after 24 Gy.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…The influence of radiation on commercial microbubbles was previously reported by Collado-Larra et al 29 Their study demonstrated that irradiating the ultrasound contrast agent SonoVue (known as Lumason in the United States) to >25 Gy, influenced its size distribution and acoustic response more than irradiated Definity. A decrease in the concentration of SonoVue bubbles with diameter < 7 μm was observed, while the acoustic scatter decreased by 3.5 dB after 24 Gy, and the acoustic attenuation increased by 0.15 dB/cm after 24 Gy.…”
Section: Resultsmentioning
confidence: 66%
“…However, Definity microbubbles did not exhibit a significant response to radiation. These findings indicate that both the components of the core and the microbubble shell might play a role in the bubbles' response to radiation 29 . In terms of PCCA, superheated PCCA of Freon 12 suspended within a wearable gel have been previously proposed as individual radiation detectors 27,30 .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…For the proton irradiations, the one-dimensional histograms were compared to a verified model of the proton Bragg peak (Bortfeld 1997). In the verification process of this model, the proton depth dose distribution was measured with a multi-layer ionization chamber (QubeNext, DE.TEC.TOR, Turin, Italy) and fitted to an analytical model of the Bragg peak, as explained in Collado-Lara et al (2021, 2022. To evaluate the proton range after bubble localization, Gaussian curves were fitted through the middle of the histogram bins for each of the bubble localization methods.…”
Section: Bubblenet-network Performance Evaluationmentioning
confidence: 99%
“…Recently, applications requiring assessment of the frequency dependency of the attenuation coefficient of microbubbles in vivo have emerged, such as to relate changes in attenuation to external factors (as in e.g., radiation dosimetry [31,32]) or to a therapeutic payload release [33]. In addition, quantitative ultrasound applications often require real-time attenuation correction methods [34,35].…”
Section: Introductionmentioning
confidence: 99%